(untitled) - Dawson, Jeremy (Los Angeles, 2017)
In Analysing Quantitative Survey Data for Business and Management Students, Jeremy Dawson introduces you to the key elements of analysing quantitative survey data using classical test theory, the measurement theory that underlies the techniques described in the book. The methodological assumptions, basic components and strengths and limitations of this analysis are explained and with the help of illustrative examples, you are guided through how to conduct the key procedures involved, including reliability analysis, exploratory and confirmatory factor analysis.
Keywords: Kinh doanh,Business; Nghiên cứu,Phương pháp thống kê,Research,Statistical methods